2019
DOI: 10.3390/su11082239
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Criteria Decision-Making Model to Choose the Best Option for Sustainable Construction Management

Abstract: The article briefly discusses the content and terms of construction project management. It identifies the main problems of construction management and discusses ways to solve those using multi-criteria methods. Well-performed management is one of the critical factors which leads to the success of any significant sustainable project. Construction project management consists of setting goals and defining user requirements, project constraints, and resources needed. This paper aims to create a practically useful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 80 publications
(62 reference statements)
0
45
0
1
Order By: Relevance
“…Therefore, we selected eight experts, five from the field of supply chain and three from academia. The selected number of experts is in accordance with the previous literature on similar studies [46][47][48]58,105,108]. The respondents' profiles are shown in Table 2.…”
Section: Data Acquisition and Sample Selectionmentioning
confidence: 96%
See 2 more Smart Citations
“…Therefore, we selected eight experts, five from the field of supply chain and three from academia. The selected number of experts is in accordance with the previous literature on similar studies [46][47][48]58,105,108]. The respondents' profiles are shown in Table 2.…”
Section: Data Acquisition and Sample Selectionmentioning
confidence: 96%
“…Therefore, scientists developed the MCDM approach, which has evolved in the 1960s, and it can solve MCDM problems in dozens of different ways. During the 1990s, management issues have got the attention of MCDM approaches and they tend to increase rapidly [108]. Studies like [47,48,109] described the development stages and applicability of MCDM in the field of economics and management science, which demonstrates its advantages over the traditional approaches for complex and uncertain situations, such as uncertainty in the environment, supply chain disruptions, stakeholder preferences, contradictory criteria, etc.…”
Section: Multi-criteria Decision-making Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The respondents who selected Layout C as the most desirable reported that it was the layout that provided the most privacy (no adjacent neighbour). This layout was ranked as the most desirable by the greatest amount of respondents (16). Layout B was reported to be the least desirable by the largest amount of respondents (19).…”
Section: Assessment Of the Analysed Urban Layoutsmentioning
confidence: 97%
“…A comprehensive overview of the suitability of the use of multi-criteria methods to assess building-integrated green technologies, ultimately using the AHP method, was featured in [15]. The same method was also used by the authors of [16] to investigate construction project management in which sustainability was deemed a key factor.…”
Section: Introductionmentioning
confidence: 99%